Understanding the nature of substance use in Zimbabwe: State of the art and ways forward: A scoping review protocol. - Blessing N Marandure; Samson Mhizha; Amanda Wilson; Clement Nhunzvi (PLoS ONE)
Reports of substance use in Zimbabwe paint a concerning picture of escalating prevalence of use, with over half of people admitted to inpatient mental health units reportedly experiencing a substance induced disorder. The country has gone through decades of significant political and socio-economical challenges, which are undoubtedly linked to the observed increases in substances use. Nevertheless, despite the resource constraints to adequately address substance use, the government has shown a renewed resolve to provide a comprehensive approach to address substance use in the country. However, there is a lack of clarity of the nature and extent of substance use and substance use disorders (SUDs), which in part is due to a lack of a national monitoring system for substance use in the country. Moreover, reports of a substance use crisis in Zimbabwe are predominantly based on anecdotal evidence, limiting the ability to gain an accurate picture of the situation. Therefore, a scoping review of the primary empirical evidence of substance use and SUDs is proposed in order to develop an adequately informed understanding of the nature of substance use and SUDs in Zimbabwe. Furthermore, the review will embed an assessment of the response to substance use, together with an analysis of the policy landscape on substance use in Zimbabwe. The PRISMA-ScR checklist will be utilised for the write up. The results of the scoping review will be essential for identifying the current state of knowledge around substance use, and identify gaps in knowledge and policy that would be a catalyst for further work to enhance knowledge and develop solutions situated within the local context. Thus the present work presents a timely effort that capitalises on current efforts by the government to address substance use in the country.